2019
DOI: 10.1109/access.2019.2894524
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Stochastic Exploration Using Grey Wolf Optimizer and Coordinated Multi-Robot Exploration Algorithms

Abstract: Multi-robot exploration is a search of uncertainty in restricted space seeking to build a finite map by a group of robots. It has the main task to distribute the search assignments among robots in real time. In this paper, we proposed a stochastic optimization for multi-robot exploration that mimics the coordinated predatory behavior of grey wolves via simulation. Here, the robot movement is computed by the combined deterministic and metaheuristic techniques. It uses the Coordinated Multi-Robot Exploration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…In the authors' previous studies [33], [34], coordinated multi-robot exploration and waypoint selection concepts [35], [36] using GWO were introduced in the probabilistic occupancy grid map. The optimization strategies in both studies showed one common drawback of such stochastic optimization methods, which is the aborted simulation runs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the authors' previous studies [33], [34], coordinated multi-robot exploration and waypoint selection concepts [35], [36] using GWO were introduced in the probabilistic occupancy grid map. The optimization strategies in both studies showed one common drawback of such stochastic optimization methods, which is the aborted simulation runs.…”
Section: Related Workmentioning
confidence: 99%
“…In the current study, a new concept for the GWO exploration algorithm is presented, which differs from the previous ones [33], [34], that is, the occupancy probabilities of cells are not applied in this study. Also, the previous studies used eight neighbor points around the robot as candidates for the next robot position.…”
Section: Algorithm 1 Grey Wolfmentioning
confidence: 99%
“…In the search process, all wolves will enhance the global exploration in the entire state space at the early evolutionary stage, while the local exploitation will be improved with the increasing number of iterations. In this way, the swarm can gradually converge to promising areas of the complex global optimization problem [51][52][53].…”
Section: B Grey Wolf Optimizer (Gwo)mentioning
confidence: 99%
“…Hiraoki Yamaguchi uses the feedback control law to coordinate the motion of multiple robots, and each robot has a formation vector to control the formations so that they capture a target by forming troop formations Oussama Hamed and Mohamed Hamlich 2 [11]. There are other methods that have been inspired from optimization algorithms [12][13][14][15]; such as Jim Pugh and Alcherio Martinoli that presented a multi-search algorithm, where they modify the Particle Swarm Optimization algorithm [16] to mimic the multi-robot search process [17]. Xialolin Luan and Yutting Sun proposed Wolf Swarm Algorithm [18], which is for encircling a target with underwater robots.…”
Section: Introductionmentioning
confidence: 99%